“Pictures in the Fire”: the Dickensian Hearth and the Concept of History - Buckland, Adelene (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractAt the symbolic centre of every Dickens novel is the roaring fire of a domestic hearth. Readers of Dickens frequently related clustering in familial groups around a fireplace, sharing in the fire’s uncertain pools of light and warmth while they read the text aloud. And within the texts themselves, the Dickens fireside has been seen as an idyllic space of conflict resolution: as Alexander Welsh has put it, “if the problem that besets” Dickens “can be called the city, his answer can be named the hearth.” This essay seeks to remember the materiality of the fireside alongside its more symbolic evocations. Comparing Dickens’s representation of the coal fuelling the fires of A Christmas Carol (1843) and Our Mutual Friend (1865), written over twenty years later, and taking in several short fictions published in Household Words in the intervening decade, it shows that Dickens often based plots of fictional transformation on the fantastic metamorphoses embodied in the lump of coal itself. While there was something exuberant about this change in the 1840s and 1850s, when Britain’s plentiful coal supplies were frequently imagined as tokens of a divine plan favourable to British industrial and imperial expansion, the darkening mood of Dickens’s late fiction chimed with contemporary fears about the waste and depletion of resources and the increasing competitiveness of the global markets. Most importantly, however, throughout his career the material dimension of coal offered Dickens both narrative possibility, and representational trouble. So important was it to his social vision that he often overlooked the cost of coal in his desire to keep his poorest characters warm, and in the 1860s he repeatedly ridiculed the national panic that Britain’s coal reserves might run out. Thinking about Dickens’s firesides as both symbolic and material spaces, fuelled by the coal whose history was of such fascination to the readers of Household Words, we see that the hearth was not only Dickens’s all-solving “answer” to the problems of the “city.” It was a space in which many of his most central concerns would sit in unequal, and unresolved, tension.